Hysto-ultrastructure of the facial nerve and mimic muscles in the norm and in the conditions of eхperimental neuropathy - V. Myhailiuk; I. Mykhailiuk; M. Hembarovskyi; O. Lebid; K. Duda; L. Patskan; N. Shovkova (Regulatory Mechanisms in Biosystems, 2017)
We studied the structural components of the facial nerve in the norm and with cold neuropathy, indicating morphological changes in neuromuscular endings and muscle fibers at 10, 15, 30 and 60 days from the beginning of the simulation of experimental neuropathy, which was caused by local supercooling of the projection portions of the extracranial parts of the facial nerve on the background of the preliminary introduction of Freud’s complete adjuvant. We established that the pathomorphological changes in the endonevral microcirculatory bed have a phase character: the initial spasm (up to 10 days) changes in paralytic vasodilation, and its residual effects remain until the end of the experiment (60 days). Changes in hemomicrocirculation conditions lead to marked disturbances in the structure of myelinic nerve fibers, which have the character of segmental demyelination with signs of delay in axonal transport and reactive restructuring of neuromuscular endings. The change in the metric composition of myelinated nerve fibers is due to an increase in the number of nerve fibers of medium and large diameters (up to 30 days) and small diameter (after 30 days). In different periods of the experiment, a decrease in the branching area of the terminal branches of the motor axon is observed in the nerve cells, local edema of the endonevria, degenerative changes in a part of the nerve fibers develop. Due to the fine-grained decay of the final nerve branches, degeneration of the motor endings took place two weeks after the start of the experiment. Neuropathy for 30 days caused a pronounced inhibition of spotting in the peripheral parts of the motor nerve fibers. After 60 days of experiment, a large number of muscle fibers underwent destructive changes. The size of a significant part of the neuromuscular endings was reduced. In all terms of cold neuropathy, neurolematocytes reacted in the same way: cytoplasm was swollen, argyrophilic grains appeared in the nuclei, fine-grained decay of individual nuclei occurred.